2009
DOI: 10.1080/13697130902957287
|View full text |Cite
|
Sign up to set email alerts
|

Breast arterial calcification is a predictive factor of cardiovascular disease in Brazilian postmenopausal women

Abstract: In postmenopausal women, breast arterial calcification may represent a higher likelihood of cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
3
12
0
4
Order By: Relevance
“…Another limitation is the primarily white, non-Hispanic participant population. Although our data may not be applicable to women of other races or ethnicities, similar studies have shown comparable results among diverse populations in areas such as Brazil, 26 Israel, 32 and the Netherlands. 19 Additionally, determination of CHD in this study was identified by patient report, which leaves open the possibility of recall bias.…”
Section: Schnatz Breast Arterial Calcifications and Chd Obstet Gynesupporting
confidence: 46%
See 2 more Smart Citations
“…Another limitation is the primarily white, non-Hispanic participant population. Although our data may not be applicable to women of other races or ethnicities, similar studies have shown comparable results among diverse populations in areas such as Brazil, 26 Israel, 32 and the Netherlands. 19 Additionally, determination of CHD in this study was identified by patient report, which leaves open the possibility of recall bias.…”
Section: Schnatz Breast Arterial Calcifications and Chd Obstet Gynesupporting
confidence: 46%
“…19 Another study, with a sample size of 307 women, reported an odds ratio of 8.13 (confidence interval [CI]: 2.7-24.6) for breast arterial calcifications in predicting women with CHD. 26 The relatively small sample sizes along with the methodologies, however, limit the conclusiveness of these recent findings. 19,26 Furthermore, the first study analyzed a marker for CHD, not CHD itself.…”
Section: Level Of Evidence: IImentioning
confidence: 99%
See 1 more Smart Citation
“…For cross-sectional studies, BAC shows high specificity for coexisting CAD/atherosclerotic CVD, ranging from 84.5% 24 to 93%. 22 The sensitivity, PPV, and NPV of BAC to detect coexisting CAD are low, with a maximum sensitivity of 50%. 25 The cohort studies also report high specificity of BAC for incident CAD morbidity and mortality (88%–97%), with low sensitivity, PPV, and NPV.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies used atherosclerotic CVD (defined as self-reported angina, history of myocardial infarction or coronary artery bypass graft, or abnormal coronary angiogram or stroke). 20,21 Ferreira et al 22 used CVD, defined as atherosclerotic CVD plus congestive heart failure. Kemmeren et al 9 used CV mortality according to the ICD-9 criteria (defined as death from coronary heart disease, cerebrovascular diseases, heart failure, complications of heart disease, or sudden cardiac death).…”
Section: Discussionmentioning
confidence: 99%